The Role of Workload in Moderating the Relationship Between Competence, Motivation, and Performance of Civil Servants in Bulungan Regency - Fitri Amin; Syahran Syahran; Muhamad Nur Utomo; Shalahuddin Shalahuddin; Ahmad Juliana (CV Edujavare Publishing, 2026)
Public sector employee performance is a key factor in achieving effective governance and high-quality public services. Amid rising public demands, government employees face job complexity, resource constraints, and high administrative pressure. This study aims to analyze the influence of competence and motivation on the performance of public sector employees and to examine the moderating role of workload in this relationship among government officials in Bulungan Regency. This study employs a quantitative approach using a survey method targeting public sector employees in Bulungan Regency. Data were collected via a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling to test the direct relationships and moderating effects among the variables, after first ensuring the validity and reliability of the instruments. The results of the study indicate that competence and motivation have a positive and significant effect on employee performance, while workload acts as a moderating variable that weakens the relationship between competence and performance as well as between motivation and performance when workload is high. These findings indicate that the management of disproportionate workloads can hinder the utilization of employees’ competencies and motivational energy; thus, in practice, local governments need to balance the distribution of workloads with competency development and motivation systems so that civil servant performance can be optimized sustainably.